Legacy Language Materials in the Ernesto Constantino Collection: Challenges and Lessons for Building a Philippine Language Archive - Or, Elsie Marie T.; Estrellado, Dustin Matthew O. (The Archive, 2024)
The late Dr. Ernesto Constantino was a prominent Filipino linguist who conducted many comparative studies on the morphology and syntax of various Philippine indigenous languages. As such, his personal collection, which was donated to the University Archives of the University of the Philippines Diliman, contains a wealth of raw data collected from different communities all over the Philippines. To date, we have cataloged 458 magnetic reel tapes and 733 cassette tapes from various linguistic fieldwork conducted by Dr. Constantino and his team of research assistants between the 1960s and the 1990s. We have also so far cataloged word and sentence lists in over a hundred Philippine language varieties. Many of these languages and dialects are under-studied while some, such as Yogad, Bolinao, and Manide, are also currently marked as threatened or endangered languages. This paper presents a preliminary assessment of the state of the legacy language materials in the Constantino Collection. We identify challenges that we face in cataloging and archiving the materials and the issues that should be faced in attempting to get subsequent use of the materials.